Effects of gabexate mesilate on coagulopathy and organ dysfunction in rats with endotoxemia. Issue 2 (March 2015) - Tsai, Hsin-Jung; Ding, Chen; Tsao, Cheng-Ming; Liao, Mei-Hui; Ka, Shuk-Man; Liaw, Wen-Jinn; Wu, Chin-Chen
<x xml:space="preserve">Abstract</x> Sepsis and its associated multiple organ failure are related to high mortality in critical patients. Several studies have reported that gabexate mesilate, a synthetic inhibitor of trypsin-like serine protease, protects tissues/organs against injury in the models of endotoxemia. The aim of this study was to examine whether gabexate mesilate could attenuate coagulopathy and organ dysfunction in lipopolysaccharide (LPS)-induced sepsis model by using thrombelastography (TEG). LPS (7.5 mg/kg/h, intravenouly for 4 h) was administered to male adult Wistar rats. Some of the LPS rats received a continuous infusion of gabexate mesilate (10 mg/kg/h, intravenously for 8.5 h) for 30 min before the LPS administration. Variable parameters of hemodynamics, biochemistry, hemostasis and inflammatory response were measured for 6 h after the LPS infusion. TEG variables (R-time, K-time, α-angle, and maximal amplitude) were also measured. The pretreatment of LPS rats with gabexate mesilate significantly attenuated the lung, liver and kidney dysfunction, consumptive coagulopathy, the increases in serum tumor necrosis factor-α, interleukin-6, plasma thrombin–antithrombin complex and plasminogen activator inhibitor-1, and neutrophils infiltration score in lung, liver and kidney, compared with the LPS alone group. In addition, TEG parameters correlated with tissue and liver injury in the late phase of endotoxemia. In particular, a strong negative correlation between maximal amplitude at 4 h and Ln (lactate dehydrogenase) at 6 h after LPS infusion was noted (r = −0.752, P < 0.001, R2 = 0.566). These results indicate that beneficial effects of anticoagulants (e.g. gabexate mesilate) in endotoxemia could be monitored by TEG per se.